Sports injuries among adolescent basketball players according to position on the court - Vanderlei, Franciele Marques; Bastos, Fabio Nascimento; De Lemes, Ítalo Ribeiro [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Júnior, Jayme Netto [UNESP]; Pastre, Carlos Marcelo [UNESP] (My University, 2013)
Background: The participation of children and adolescents in sports, including basketball, is becoming increasingly common, and this increased involvement raises concerns about the potential risk of sports injuries. Objective. To analyze the occurrence of sports injuries among young basketball players according to their position on the court and to associate these injuries with risk factors. Method. A retrospective, epidemiological study. A sample consisting of 204 basketball players with a mean age of 14.33 ± 1.19 years participated in the study. The players were interviewed using a reported condition questionnaire containing anthropometric and training data as well as information on injuries during the previous 12 months. Results: The frequency of injury was highest among the shooting guards (47.8%), followed by the centers (34.8%) and point guards (17.4%). Among the 204 participants, 40 players reported a total of 46 injuries, representing 0.22 injuries per participant and 1.15 injuries per injured participant. For the shooting guards and centers, statistically significant differences between injured and non-injured players were found related to age, weight, height, length of time in training and number of weekly practice hours (p < 0.05). For point guards, a statistically significant difference between injured and non-injured players was found based on weight alone (p < 0.05). Conclusion: The occurrence of injuries among basketball players was low. Injuries were associated with both intrinsic and extrinsic factors among shooting guards and centers, whereas injuries were only associated with weight among point guards. © 2013 Vanderlei et al; licensee BioMed Central Ltd.
Keywords: Morbidity surveys; Risk factors; Trauma in athletes; adolescent; age; basketball; body height; body weight; childhood injury; female; human; incidence; interview; major clinical study; male; physical activity; questionnaire; retrospective study; risk assessment; risk factor; sport injury; training